Studies on phytochemicals, antibacterial and Antioxidant effects of leaf extracts of Lamprachaenium microcephalum - Mohana Sundaram; Sivakumar; Karthikeyan; Magesh; Gopinath; Sheeladevi; Thirumalai; Pennarasi; Prasanna (Journal of Research in Biology, 2011)
In this investigation, Lamprachaenium microcephalum was analysed for its phytochemical constituents qualitatively and quantitatively. The antibacterial property of aqueous, ethanolic and hexane extracts of Lamprachaenium microcephalum was studied against different bacteria include Escherichia coli, Proteus mirabilis, Salmonella typhi, Enterobacter aerogenes, and Shigella flexineri and showed growth inhibition activity at concentrations in the range of 300mg to 500mg. The antioxidant effect of those extracts was also studied against α-tocopherol as a control. From the results, Alkaloids, flavonoids, saponins, and tannins were revealed to be present in Lamprachaenium microcephalum. Ethanol extract at the concentration of 500μg/ml showed 61.16% antioxidant activity against 500 μg/ml of α-tocopherol which showed 76.86% as a standard reference